Natural vibration of an aqueous pendant drop - Parkinson, L.; Phan, Chi (Elsevier Science Inc., 2018)
Interfacial dynamics of a pendant drop suspended from a needle support was studied via a new experimental method, without external excitation, to accurately quantify the impact of size and surface properties on the natural frequency. For drops ranging between 3.0 and 40.2 mm 3 , the natural frequency of vibration varied proportionally to the volume raised to the exponent -3/4, V -3/4 . A direct relationship between the frequency and the water drops was obtained f(Hz) ? S - 3/4 t c -1 , in which S is the dimensionless size parameter. Previous works performed employing external excitation suggested a direct impact of the supporting size, which might be explained by the acting force. The current experimental results do not follow this prediction, indicating insignificant influence of the support base on the recorded frequency. The results indicate a significant role of surface tension, which is taken into account by size factor S, on the vibration of the pendant drop.